ANALISIS KANDUNGAN SERAT PANGAN DAN DAYA TERIMA FORMULA MINUMAN HEALTHY BOBA - Hasina Nur Fajrin; Mohammad Jaelani; Yuwono Setiadi; Ria Ambarwati (Poltekkes Kemenkes Semarang, 2022)
Background: Boba milk tea is a drink that contains high calories, sugar and fat and low fiber which can increase the risk factors for high blood sugar disorders. It needs to be modified by adding porang glucomannan flour and kappa carrageenan as high-fiber food ingredients. Objective: To determine the dietary fiber content and the acceptability of the healthy boba drink formula.Method: The study used a true experimental method with a one-factor completely randomized design (CRD) with three treatments. Food fiber content data were analyzed using One Way ANOVA and Post Hoc Duncan Multiple Range Test (DMRT). Acceptance data was analyzed using the Kruskal-Wallis Test. Results: The dietary fiber content of 1 serving of Healthy Boba drink formula is F1 (1.1663 g), F2 (1.8079 g), F3 (1.7527 g). Variations in the addition of glucomannan porang flour and kappa carrageenan had a significant effect on the dietary fiber content of the Healthy Boba Drink formula (p=0.000). There was no difference in panelists' acceptance of color (p=0.977), aroma (p=0.846), taste (p=0.109) and texture (p=0.148). The level of acceptance of the Healthy Boba drink is 90% of consumers can spend 75% of the portion of F1, 77% in F2 and 73% in F3. Conclusion: The highest dietary fiber content in the Healthy Boba Drink formula can meet 4.9% of the fiber needs in prediabetes adolescents, and can be recommended as an alternative drink in the prevention of prediabetes.